Individual Energy Consumption Behavior Leads to Energy Sustainability in Malaysia - Abdullah, M.R.T.L. (MDPI, 2022)
Malaysia ranks third in the world in terms of carbon emissions, with an average annual rate of 4.7 percent. There is a strong need to understand the challenges and motivations for energy consumption change at the individual level. This study aims to investigate the relevant factors affecting Malaysian individual energy consumption behavior towards energy sustainability using the multi-criteria decision-making methodology of the Analytic Hierarchy Process (AHP). The data were collected from 121 experts using a purposive sampling technique. A framework is developed by assigning weight to the selected factors and sub-factors based on their relative importance in pairwise comparison matrices. The results showed that there were five main factors influencing individual energy consumption behavior in Malaysia, where education was ranked as the top priority, followed by institutions, social values and norms, social structure, and lastly, lifestyle. There were also 16 relevant sub-factors ranked from top priority to least priority (environmental concern, ecology knowledge, energy policy, environmental consciousness, energy tariff, energy efficient technology, morals, social class, location, culture, ethics, choice of lifestyle, personal materialism, gender, ethnicity, and spirituality). Policymakers will be in a better position to design intervention strategies for energy sustainability through energy policy if they understand individual consumption behavior. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.